Identification and resistance profile of gram positive bacteria from aquatic environment (Research, Society and Development, 2021)
The Meia Ponte River – Goiás/Brazil, is responsible for benefiting about 2 million people in Goiás State. However, the increase in pollution with the disposal of sewage, chemicals and drug remains have contributed to the increase in bacterial resistance and the exchange of resistance genes. The objective of this study was to isolate, identify and analyze the resistance profile of gram-positive bacteria present in raw water and sediment of the Meia Ponte River – Goiás. The samples were collected from four sampling points and two collections were carried out, one in the dry season and the other in the rainy season. The isolated bacteria were identificated, then the antibiogram was performed. A total of 75 strains were isolated, 72.0% (54/75) of Streptococcus spp., 12.0% (9/75) of Staphylococcus spp., 9.3% (7/75) of Bacillus spp. and 6.7% (5/75) of Enterococcus spp. Furthermore, 52.0% (39/75) of the isolated strains were from raw water and 48.0% (36/75) were isolated from the sediment. Among the samples, strains of Staphylococcus spp. and Bacillus spp. showed greater resistance to antimicrobials, on the other hand, Enterococcus spp. showed less resistance. Some strains of Bacillus spp. and Streptococcus spp. presented multidrug resistant, Staphylococcus spp. showed multidrug resistant and some pan-drug resistant. In the correlation of Spearman Staphylococcus spp. and Streptococcus spp. isolated, were the ones that presented the most significant correlations (p < 0.05). Thus, the study shows the importance of ascertaining the resistance profile of this group of bacteria that aquatic environment.